Stage of Cognitive Mathematics Students Development Based on Piaget's Theory Reviewing from Personality Type - Rahmad Sugianto; Rani Darmayanti; Annisa Nurina Vidyastuti (Institut Pendidikan Indonesia, 2022)
Penelitian ini bertujuan untuk menelaah kesesuaian tahap perkembangan kognitif Piaget ditinjau dari tipe kepribadian terhadap siswa kelas X SMA Wachid Hasyim 2 Taman. Subjek dari penelitian ini adalah siswa sebanyak 25 orang dengan usia antara 12 sampai 16 tahun. Penelitian ini menggunakan instrumen Test of Logical Operations (TLO) dalam matematika dan Tes Myers-Briggs Type Indicator (MBTI). TLO terdiri dari 14 soal dan siswa diberi waktu menjawab semua soal selama 45 menit sedangkan MBTI terdapat 60 pernyataan dan siswa diberi waktu 30 menit untuk memberikan pernyataan yang sesuai dengan kepribadiannya. Hasil penelitian menunjukkan 28,5% siswa ekstrovert pada tahap operasi konkrit awal dan 71,5% pada tahap operasi konkrit akhir. Sedangkan 27,2% siswa introvert pada tahap operasi konkrit awal dan 72,8% pada tahap operasi konkrit akhir. Skor rata-rata TOL Piaget memiliki nilai yang sama pada siswa ekstrovert dan introvert yakni 47 yang artinya rata-rata siswa cenderung pada tahap konkrit akhir. Perbedaan pemahaman antara rata-rata siswa ekstrovert dan introvert pada tipe seration, dimana rata – rata siswa ekstrovert pada pemahaman tinggi sedangkan siswa introvert pada pemahaman cukup.This study aims to examine the suitability of Piaget's stage of cognitive development in terms of personality type for class X students of SMA Wachid Hasyim 2 Taman. The subjects of this study were 25 students with ages between 12 to 16 years. This study uses the Test of Logical Operations (TLO) instrument in mathematics and the Myers-Briggs Type Indicator (MBTI) test. The TLO consists of 14 questions and students are given 45 minutes to answer all questions, while the MBTI contains 60 statements and students are given 30 minutes to give statements that match their personality. The results showed that 28.5% of students were extroverted in the early concrete operations stage and 71.5% in the late concrete operations stage. While 27.2% of students were introverted at the initial concrete operation stage and 72.8% at the final concrete operation stage. The average score of Piaget's TOL has the same value for extroverted and introverted students, namely 47, which means that the average student tends to be in the final concrete stage. The difference in understanding between the average extroverted and introverted students in the compatible type, where the average extrovert student has high understanding while introverted students have sufficient understanding.